Research progress on phosphodiesterase 4 inhibitors in the treatment of palmoplantar pustulosis - YAO Xinyi; Gao Wenli; LI Juan; ZHANG Junling (Pifu-xingbing zhenliaoxue zazhi)
Palmoplantar pustulosis (PPP) is a chronic recurrent inflammatory skin disease. Existing therapeutic methods cannot meet the demand by patients. Phosphodiesterase-4 (PDE-4) is a key enzyme involved in the balance of immunocytes. It acts as a downstream mediator in the signaling pathways of a variety of cytokines which are associated with palmoplantar pustulosis and extensively regulate immune responses. Apremilast, as representative of the oral PDE-4 inhibitors, displays superior efficacy in clinical trials against palmoplantar pustulosis. Crisaborole has also been regulate to induce sustained improvement in skin lesions. This article reviews the research progress on PDE-4 inhibitors in treatment of palmoplantar pustulosis.